Copper-Catalyzed Intramolecular Desymmetric Aryl CO Coupling for the Enantioselective Construction of Chiral Dihydrobenzofurans and Dihydrobenzopyrans - Yang, Wenqiang; Liu, Yangyuan; Zhang, Shasha; Cai, Qian (Angewandte Chemie, 2015)
O‐Heterocyclic structures such as 2,3‐dihydrobenzofurans are key motifs in many natural compounds and pharmaceuticals. Enantioselective formation of chiral dihydrobenzofurans and analogues was achieved through a copper‐catalyzed desymmetrization strategy with a chiral cyclic 1,2‐diamine. A broad range of substrates are compatible with this CuI‐diamine catalytic system and afford the desired coupling products with chiral tertiary or quaternary carbon centers in high yields and good to excellent enantioselectivities under mild conditions. O‐Heterocyclen wie chirale Dihydrobenzofurane wurden durch eine kupferkatalysierte Desymmetrisierung mit einem chiralen cyclischen 1,2‐Diaminliganden enantioselektiv hergestellt. Eine Reihe von Substraten ist mit diesem CuI‐Diamin‐Katalysesystem kompatibel und liefert die Kupplungsprodukte mit chiralen tertiären oder quartären Kohlenstoffzentren unter milden Bedingungen in hohen Ausbeuten und guten bis sehr guten Enantioselektivitäten.